The labour market drop-out rate : a new approach to estimating the returns to government investment in higher education : the case for marine science in South Africa - Grootes, Pieter Brian (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2005)
The private and social returns to education literature share the same conclusion: that education is beneficial for both the individual and society. However, the theoretical underpinnings are flawed as the literature does not account for the main feature that leads to the acquisition of education: the private demand for education. An understanding of the factors that motivate the individual to invest in education would lead to a deeper insight as to why both private and social returns to education exist, and would provide a clearer framework on which to base the government funding of education. This thesis provides a first attempt at filling this gap by introducing a method of estimating the returns to government investment in education, which is labelled the 'labour market drop-out rate approach'. The approach focuses on the social return to education, not in terms of graduate earnings, but in terms of the interaction of the graduate with the economy. The approach introduces a measure of expertise utilisation, based on the premise that there is no social return to an individual acquiring education if he or she does not utilise the acquired knowledge base on entering the labour market. The approach is tested using the labour market for marine scientists in South Africa as a case study. In this case the private demand for education is found to be heavily influenced by the provision of student bursaries from the National Research Foundation, with a resulting estimate of the social return to a degree in marine science being a mere 20% to 25%. Owing to this, a new approach to government investment in marine science is introduced, that of graduate contribution schemes. Of broader significance is the ease of application of this approach, it may be adopted to analyse any funding programme in which a government may decide to invest. As such, the labour market drop-out rate provides an extension to the returns to education literature through its theoretical dealings of the private demand for education, as well as a practical tool which government agencies can use to evaluate the efficacy of any government funding of education.
Keywords: Labor market; Marine scientists -- South Africa; Education -- Economic aspects -- South Africa; Higher education and state -- South Africa; Education -- Social aspects; Human capital -- South Africa; Education, Higher -- Economic aspects -- South Africa